A New Look at Gaia's Relationship with Water. (27th September 2017) - Champoux, Peter
Abstract: An exploration of the interconnectedness of the geometries of a water molecule, the geologic and geographic regions of our planet, and the universe as a whole. Water is shown as a crucial "bridge" passing from the microscopic to the stellar and interstellar.